2007
DOI: 10.1021/nl0716000
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Nanoparticle Shape Effects on Benzene Hydrogenation Selectivity

Abstract: Benzene hydrogenation was investigated in the presence of a surface monolayer consisting of Pt nanoparticles of different shapes (cubic and cuboctahedral) and tetradecyltrimethylammonium bromide (TTAB). Infrared spectroscopy indicated that TTAB binds to the Pt surface through a weak C-H...Pt bond of the alkyl chain. The catalytic selectivity was found to be strongly affected by the nanoparticle shape. Both cyclohexane and cyclohexene product molecules were formed on cuboctahedral nanoparticles, whereas only cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
742
1
14

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 833 publications
(775 citation statements)
references
References 18 publications
18
742
1
14
Order By: Relevance
“…Benzene hydrogenation studies on cubooctahedra and cubic Pt nanoparticles demonstrated that cyclohexene and cyclohexane formed on cuboctahedral nanoparticles, while only cyclohexane formed on cubic nanoparticles, consistent with previous results for single-crystal Pt surfaces ( Figure 11) 46 . This study indicates the importance of nanoparticle shape in determining reaction selectivity.…”
Section: Shape Dependence Of Pt Nanoparticlessupporting
confidence: 91%
See 1 more Smart Citation
“…Benzene hydrogenation studies on cubooctahedra and cubic Pt nanoparticles demonstrated that cyclohexene and cyclohexane formed on cuboctahedral nanoparticles, while only cyclohexane formed on cubic nanoparticles, consistent with previous results for single-crystal Pt surfaces ( Figure 11) 46 . This study indicates the importance of nanoparticle shape in determining reaction selectivity.…”
Section: Shape Dependence Of Pt Nanoparticlessupporting
confidence: 91%
“…That is, if there are several thermodynamically stable products, only one desired product is formed [44][45][46] . We have investigated some typical multipath reaction selectivities: benzene and cyclohexene hydrogenation.…”
Section: Size Dependence Of Pt Nanoparticlesmentioning
confidence: 99%
“…For instance, both cyclohexene and cyclohexane formed on cuboctahedral nanocrystals during benzene hydrogenation / dehydrogenation while only cyclohexane formed on cubic nanocrystals. 6 These observations were consistent with previous results for Pt single-crystal studies. In order to further investigate the roles of nanocrystal size and shape in transition metal heterogeneous catalysis, it is essential to simultaneously control the size and the shape of the nanocrystals.…”
Section: Introductionsupporting
confidence: 93%
“…6,7 Several synthetic methods for cubic Pt nanocrystals were reported previously, however, sizes of these shaped nanocrystals were typically around 10 nm or larger. [7][8][9][10] Sub-10 nm nanocrystals demonstrate different physical and chemical properties from large nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by using NaBH 4 to reduce K 2 PtCl 4 , Pt nanocubes were formed. 38 However, if a milder reducing agent such as ascorbic acid was used, Pt nanodendrites were produced. 114,115 Thermodynamic control can be achieved by altering the surface energy of prepared materials.…”
Section: Developments Of the Synthetic Methodsmentioning
confidence: 99%